Immunological responses of sheep against adult worm extract antigen of Fasciola gigantica - Widjajanti, S (Indonesian Animal Sciences Society, 1999)
Immunological responses of sheep against adult worm extract antigen of Fasciola gigantica were evaluated in an effort to identify the protein antigen for the candidate of vaccine. In this study the protein antigen from adult worms was extracted, and the extract antigen was then intramuscularly injected into 4 groups of 5 sheep. Two groups received one injection, these included one group injected only with extract antigen and the other group injected with extract antigen emulsified in Quil A adjuvant. The other two groups received two injections with a two week interval, these included one group injected only with extract antigen and the other group injected with extract antigen emulsified in Quil A adjuvant. Three weeks later all of the sheep were challenged with 300 metacercariae of F. gigantica. The antibody titer was monitored every two weeks by using ELISA and the protein profile from each group was compared by using western blotting. Fifteen weeks after challenged all of the sheep were killed and the liver flukes were collected from the liver and counted. The results showed that the antibody titer was higher in the group which received two injections, and the additional of Quil A adjuvant gave much better protection from the infection of F. gigantica (57%) and could avoid the death of the sheep than twice injection of antigen without Quil A adjuvant (37%). Â Key words : Fasciolosis, Fasciola gigantica, protein antigen, antibody responses, vaccine